(untitled) (Journal of Pathology of Nepal, 2024)
Testing for vitamin D deficiency increased over the past years among Nepalese population. The aim of this study is to investigate the trends in the incidence of testing for vitamin D and the prevalence of patients with circulating concentrations of Vitamin D indicative of toxicity (>100 nmol/L) between 2015 and 2022.